Stroke and the risk of gastrointestinal disorders: A Mendelian randomization study - Song, Jingru; Chen, Wenjing; Ye, Wei (Frontiers in Neurology, 2023)
Background: The issue of whether stoke is causally related to gastrointestinal disorders was still not satisfactorily understood. Therefore, we investigated if there is a connection between stroke and the most prevalent gastrointestinal disorders, including peptic ulcer disease (PUD), gastroesophageal reflux disease (GERD), irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD). Methods: We applied two-sample Mendelian randomization to investigate relationships with gastrointestinal disorders. We obtained genome-wide association study (GWAS) summary data of any stroke, ischemic stroke, and its subtypes from the MEGASTROKE Consortium. From the International Stroke Genetics Consortium (ISGC) meta-analysis, we acquired GWAS summary information on intracerebral hemorrhage (ICH), including all ICH, deep ICH, and lobar ICH. Several sensitivity studies were performed to identify heterogeneity and pleiotropy while inverse-variance weighted (IVW) was utilized as the most dominant estimate. Results: No evidence for an effect of genetic predisposition to ischemic stroke and its subtypes on gastrointestinal disorders was found in IVW. Complications of deep ICH are a higher risk for PUD and GERD. Meanwhile, lobar ICH has a higher risk of complications for PUD. Conclusions: This study provides proof for the presence of a brain-gut axis. Among the complications of ICH, PUD and GERD were more common and associated with the site of hemorrhage.